An ultrasensitive UPLC-MS/MS assay for the quantification of the therapeutic peptide liraglutide in plasma to assess the oral and nasal bioavailability in beagle dogs - Sauter, Max; Uhl, Philipp; Majewsky, Marius; Fresnais, Margaux; Haefeli, Walter E.; Burhenne, Jürgen (Bioanalysis, 2019)
Aim: An ultrasensitive UPLC-MS/MS assay for liraglutide was developed and validated according to US FDA and EMA guidelines and applied to the quantification of plasma concentrations after intravenous, nasal and oral administration of liraglutide to beagle dogs. Results: Liraglutide isolation was performed with a combined protein precipitation and solid-phase extraction protocol. The calibrated concentration range of 0.1-200 ng/ml was linear with correlation coefficients >0.998. Precise analysis was achieved through the utilization of an isotopically labeled internal standard. Absolute bioavailability of liraglutide after nasal and oral administration of liraglutide to beagle dogs was 0.03 and 0.006%, respectively. Conclusion: The assay matches the performance in sensitivity of the previously applied immunoassay and optimally covers the therapeutic range of liraglutide.